2011
DOI: 10.1208/s12249-010-9554-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Commercially Available Bortezomib Products: Differences in Assay of Active Agent and Impurity Profile

Abstract: The analytical properties of two commercially available bortezomib products (VELCADE® and Bortenat) were compared using nuclear magnetic resonance, mass spectrometry, high-performance liquid chromatography, and gas chromatography. The data showed differences between the two products. Based on these data, Bortenat samples contained more active ingredients than indicated by the label (mean, 116.5% and 117.9% of label, in 2-mg and 3.5-mg vials, respectively). In comparison, VELCADE samples contained a mean of 99.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The low aqueous solubility and poor chemical stability of bortezomib was an issue in its formulation development. [3][4][5][6][7][8] For example, the intravenous and current subcutaneous formulation of bortezomib is a lyophilized formulation from 1% mannitol where mannitol ester formation was confirmed. [3][4][5] The solubility of bortezomib in water is about 0.5-0.6 mg/mL, whereas in the presence of 1% mannitol, a solubility of 4 mg/mL has been reported because of ester formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low aqueous solubility and poor chemical stability of bortezomib was an issue in its formulation development. [3][4][5][6][7][8] For example, the intravenous and current subcutaneous formulation of bortezomib is a lyophilized formulation from 1% mannitol where mannitol ester formation was confirmed. [3][4][5] The solubility of bortezomib in water is about 0.5-0.6 mg/mL, whereas in the presence of 1% mannitol, a solubility of 4 mg/mL has been reported because of ester formation.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in boronic acid derivatives as drugs has increased since the introduction and approval of bortezomib, a drug used to treat multiple myeloma, and boronophenylalanine, or BPA, a clinically useful agent for boron neutron capture cancer therapy. The low aqueous solubility and poor chemical stability of bortezomib was an issue in its formulation development . For example, the intravenous and current subcutaneous formulation of bortezomib is a lyophilized formulation from 1% mannitol where mannitol ester formation was confirmed .…”
Section: Introductionmentioning
confidence: 99%
“…306 Byrn et al propose different methods to compare the contents and impurity profile of two pharmaceutical formulations available on the US market. 563 The presence of an additional impurity as well as a different inactive/active form ratio between the two formulations demonstrated that they were not strictly equivalent.…”
Section: Proteasome Inhibitormentioning
confidence: 99%
“…In India there is another commercially available bortezomib product called Bortenat (Natco Pharma, Hyderabad, India), reportedly containing substantially more active entity than declared, potentially resulting in increased toxicity [128].…”
Section: Regulatory Affairsmentioning
confidence: 99%